Peran Teknologi Informasi Dalam Peningkatan Kualitas Pendidikan IPAS: Studi Kasus MI Darussalam, Pasir Pengaraian Rokan Hulu, Riau - iin Gusmana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to analyze the role of information technology in improving the quality of Natural and Social Sciences (IPAS) education at MI Darussalam, Pasir Pengaraian, Rokan Hulu, Riau. The study employed a qualitative approach using a case study design. Research participants consisted of the principal, IPAS teachers, classroom teachers, and students selected through purposive sampling. Data were collected through observations, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings reveal that information technology plays a significant role in enhancing the quality of IPAS learning through the use of educational videos, digital media, internet resources, and interactive presentations. The integration of information technology was found to increase students’ learning motivation, classroom participation, conceptual understanding, and twenty-first-century skills such as digital literacy, critical thinking, creativity, and independent learning. Furthermore, information technology supports the effectiveness of teaching practices and educational management within the madrasah. Supporting factors include strong leadership from the principal, the availability of technological facilities, and teachers’ readiness to adopt digital tools, while challenges include limited digital infrastructure, unstable internet connectivity, and varying levels of teachers’ digital competence. This study concludes that information technology is a strategic instrument for improving the quality of IPAS education in Islamic elementary schools and promoting innovative, interactive, and future-oriented learning environments.